Analisis Pengaruh Pertumbuhan Ekonomi Dan Kesempatan Kerja Terhadap Tingkat Kemiskinan Di Kota Jayapura Tahun 2007-2021 - Helena Gracelia U. Gobay; Yundy Hafizrianda; Sarlota A. Ratang (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2022)
The purpose of this study was to determine the effect of economic growth and employment opportunities on poverty levels in Jayapura city. This study uses time series data, and the data analysis method used is multiple regression. In the results of the study, it was found that the value of the regression coefficient of the economic growth variable was 0.000 with a significance level of 7.381. So it can be concluded that economic growth has a positive and significant effect on the level of poverty. The regression coefficient value of the employment level variable is 0.031, with a significance level of 2.440. So it can be concluded that the level of employment has a positive and significant effect on the poverty rate in Jayapura City. Keywords: poverty rate, economic growth, employment opportunity level. Keywords: employment opportunity level, economic growth, and poverty rate